2018
DOI: 10.1002/pd.5223
|View full text |Cite
|
Sign up to set email alerts
|

Predicting fetoplacental chromosomal mosaicism during non‐invasive prenatal testing

Abstract: This approach permits the non-invasive detection of fetal autosomal aneuploidies and identifies pregnancies with a high risk of fetoplacental mosaicism. Knowledge about the presence of chromosomal mosaicism in the placenta influences risk estimation, genetic counseling, and improves prenatal management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
52
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 40 publications
5
52
0
3
Order By: Relevance
“…Most of the rare autosomal aneuploidies detected by NIPT were false positives, and they did not affect the fetus. Confined placental mosaicism (CPM) was suspected in most cases because no structural abnormalities were identified by prenatal ultrasound examination or clinical follow‐up in these patients. Similar to a previous report on incidence of trisomic CPM in diagnostic chorionic villus sampling procedures, extra copies of chromosome 7 was the most common one found in our study.…”
Section: Discussionsupporting
confidence: 92%
“…Most of the rare autosomal aneuploidies detected by NIPT were false positives, and they did not affect the fetus. Confined placental mosaicism (CPM) was suspected in most cases because no structural abnormalities were identified by prenatal ultrasound examination or clinical follow‐up in these patients. Similar to a previous report on incidence of trisomic CPM in diagnostic chorionic villus sampling procedures, extra copies of chromosome 7 was the most common one found in our study.…”
Section: Discussionsupporting
confidence: 92%
“…[39][40][41] Ethical issues on reporting these sometimes nonsevere abnormalities aside, the incorporation of FF in statistical outcome-which is generally not done with, eg, the popular z-score approach-does improve performance. 42,43 Indeed, our study was concluded by revealing that 0.71% of all NIPT samples significantly differed from the healthy gonosomal trend; however, when evaluating these outliers in relation to predicted FF, only a few truly met the requirements to suffice as being potentially sex aneuploid.…”
Section: Preface Indirectly Hints Towards Potential Sex Aneuploidiesmentioning
confidence: 78%
“…The runner‐up, in second place, is Nathalie Brison for Predicting fetoplacental chromosomal mosaicism during noninvasive prenatal testing, published in the March issue.…”
Section: The Malcolm Ferguson‐smith Award: Winning Authors and Articlesmentioning
confidence: 99%